2013
DOI: 10.1175/jcli-d-12-00496.1
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Meridional Overturning Circulation (AMOC) in CMIP5 Models: RCP and Historical Simulations

Abstract: The Atlantic meridional overturning circulation (AMOC) simulated by 10 models from phase 5 of the Coupled Model Intercomparison Project (CMIP5) for the historical (1850–2005) and future climate is examined. The historical simulations of the AMOC mean state are more closely matched to observations than those of phase 3 of the Coupled Model Intercomparison Project (CMIP3). Similarly to CMIP3, all models predict a weakening of the AMOC in the twenty-first century, though the degree of weakening varies considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
289
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(343 citation statements)
references
References 36 publications
54
289
0
Order By: Relevance
“…A similar weakening in the AMOC strength has also been simulated in historical CMIP5 runs (e.g. Drijfhout et al 2012;Cheng et al 2013). There is no clear imprint of the solar irradiance or volcanic eruptions (Ortega et al 2012), which are the dominant natural forcings at decadal and longer time scales (Fernández-Donado et al 2013).…”
Section: Amoc Variabilitysupporting
confidence: 75%
See 2 more Smart Citations
“…A similar weakening in the AMOC strength has also been simulated in historical CMIP5 runs (e.g. Drijfhout et al 2012;Cheng et al 2013). There is no clear imprint of the solar irradiance or volcanic eruptions (Ortega et al 2012), which are the dominant natural forcings at decadal and longer time scales (Fernández-Donado et al 2013).…”
Section: Amoc Variabilitysupporting
confidence: 75%
“…Yet these reconstructions generally disagree with the one in Lund et al (2006). Rahmstorf et al (2015), for example, showed instead an AMOC weakening during the industrial period as compared to the LIA, in agreement with results from instrumental records (Dima and Lohmann 2010) and CMIP5 historical model simulations (Drijfhout et al 2012;Cheng et al 2013;Jungclaus et al 2014). These latter however generally disagree on the mechanisms underlying the AMOC variability, as well as on the AMOC sensitivity to external forcing (e.g., Servonnat et al 2010;Ortega et al 2012;Hofer et al 2011).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The pattern and magnitude of the trends are very similar in the CESM-LENS ensemble mean including an absence of warming to the southeast of Greenland but with stronger warming in the Bering Sea and Greenland Sea (Figure 1b). The lack of warming south of Greenland results from a reduction in the poleward transport of warm water in the upper ocean by the Atlantic meridional overturning circulation (AMOC) and lengthened exposure to surface cooling as sinking at high latitudes decreases (Drijfhout et al, 2012;Cheng et al, 2013).…”
Section: Sst Trendsmentioning
confidence: 99%
“…Additionally, errors could result from a lack of atmospheric processes in the models i.e. an underestimation of low cloud cover is a cause of significant errors in radiative fluxes (Kauker 2003), as the SST response to shortwave radiative forcing is thermally direct (Cheng et al 2013) and lowlevel stratiform liquid and mixed-phase clouds are found to be the most important contributors to the Arctic surface radiation balance (Shupe and Intrieri 2004). Another explanation could be the sea ice export and variation, so the changes of albedo and fresh water input of the area, during the 50 years of study (Halvorsen et al 2015).…”
Section: Rmse Mean Bias and Variancementioning
confidence: 99%